HUBUNGAN PENGETAHUAN DAN SIKAP PERAWAT TENTANG KESELAMATAN PASIEN DENGAN KEPATUHAN MELAKSANAKAN TINDAKAN PENCEGAHAN PASIEN JATUH DI RUANG INSTALASI GAWAT DARURAT RSUD KABUPATEN LOMBOK UTARA - Alwan Wijaya; Ni made sumartiyawati; Silviana Ananda dewi (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Nurses' knowledge and attitudes about patient safety are the understanding, skills, and mental predispositions that nurses have in guaranteeing patient safety, including adherence to standard procedures, infection prevention, risk management, and a commitment to continuously improve patient safety practices. Objective: to determine the relationship between the knowledge and attitude of nurses regarding patient safety and compliance in implementing measures to prevent patients from falling in the Emergency Installation Room of the North Lombok Regency Hospital. Methods: This type of research is a quantitative research with a cross sectional approach. The population in this study is 22 emergency room nurses. The sample in this study was 22 people using the Total sampling method. The data collection technique uses a questionnaire. Data analysis uses the Spearman's Rank Correlation test. Results: Statistical analysis showed that there was a relationship between nurses' knowledge and compliance with implementing fall prevention measures, p=0.001 (α<0.05). And there was no relationship between nurses' attitudes and compliance with implementing measures to prevent patients from falling, p=0.760 (α<0.05). Conclusion: There is a relationship between nurses' knowledge and compliance with implementing patient fall prevention measures. And there is no relationship between the attitude of nurses and compliance in implementing preventive measures for patients to fall in the emergency room of the North Lombok Regency Hospital.